Proliferative activity of osteosarcoma cells: comparison of osteoblastic and nonosteoblastic regions - Sakayama, Kenshi; Fujibuchi, Taketsugu; Kidani, Teruki; Miyazaki, Tatsuhiko; Yamamoto, Haruyasu (Journal of orthopaedic science : official journal of the Japanese Orthopaedic Association, 2003)
There are two opinions regarding malignancy evaluation by location for osteoblastic osteosarcoma: One is that the nonosteoblastic region is undifferentiated and the degree of malignancy is high; the other is that the osteoblastic region sometimes shows a marked chemotherapy effect, so the degree of biological malignancy is higher. To clarify this point, we compared and examined the difference in growth ability at intratumoral locations within the same tumor using proliferating cell nuclear antigen (PCNA) immunohistochemical staining and argyrophilic nucleolar organizer regions (AgNORs) staining. The subjects were 10 patients with osteoblastic osteosarcoma at the distal region of the femur. Specimens obtained during surgery were stained with PCNA and AgNORs, after which about 2400 tumor cells were counted per field of view, respectively. In all patients, the nonosteoblastic region showed a higher value than the osteoblastic region for both the PCNA labeling index and AgNORs number. A positive correlation was observed between the PCNA labeling index and the AgNORs number. Both the PCNA-labeling index and AgNORs number in the metastatic foci were higher than in the primary lesions. There are differences in proliferative ability in the intratumoral locations within the same osteoblastic osteosarcoma. Moreover, there are differences in proliferative ability between the metastatic foci and the primary lesion.